Impaired sperm chromatin integrity in obese mice. (24th January 2014) - Duale, N.; Steffensen, I.‐L.; Andersen, J.; Brevik, A.; Brunborg, G.; Lindeman, B.
Abstract An increased global prevalence of obesity coincides with an apparent decline in male sperm quality and a possible association between these pathologies has been suggested. In this study, we examined the effects of obesity on sperm chromatin integrity using two mouse models of obesity. In one group of mice, obesity was induced by a high‐fat diet (HFD) (diet‐induced obesity; DIO model), whereas in the other group, leptin deficiency was used to study the effects of obesity independently of the influence of dietary factors. Sperm chromatin integrity is recognized as an important measure of male infertility, and was analysed by the sperm chromatin structure assay. We found increased sperm DNA fragmentation in both groups of obese mice compared to lean mice, whereas the percentage of immature spermatozoa was not increased by obesity. The DIO model reflects the human condition more closely than the leptin‐deficient model and was therefore selected for examination of the transcriptional response of a selection of marker genes in the testis by quantitative real‐time PCR. The analysis of transcript levels of the selected testicular marker genes showed moderate, but significant, up‐regulation of the Cyp2e1, Cyp19a1, Tnf and Pparg genes in DIO mice compared to lean mice. In conclusion, a clear positive correlation between body mass index and sperm DNA fragmentation was found in two mouse models of obesity. However, the variability in sperm DNA fragmentation within the two groups of obese animals was high. The observed changes in the transcript level of the marker genes suggest that there may be a local response in testicular cells to the HFD regimen with a potential impact on intratesticular signalling and spermatogenesis.